Analysis of subjective acoustic measures and speech intelligibility in Portuguese churches - António P. O. Carvalho (1996)
This study reports on subjective acoustical field measurements made in a survey of 36 Catholic churches inPortugal built in the last 14 centuries. The same group of college students were asked to judge the qualityof speech and music at all the churches. Two sets of listeners in each church evaluated live musicperformance (cello and oboe) at two similar locations in each of the rooms using a seven-point semanticdifferential rating scale. An acoustical evaluation sheet was used to measure listeners overall impression ofroom acoustics qualities, and each of the factors that can contribute to that perception as loudness,reverberance, intimacy, envelopment, directionality, balance, clarity, echoes and background noise.Speech intelligibility tests were also given to the same group in each church. One-hundred-word lists wereused in live speech tests using a theater college student as speaker. The results are graphed and analyzedby comparisons. Variations of subjective and speech intelligibility qualities were identified among thedifferent churches and within each of the churches as well. The subjective qualities that contributed tooverall acoustical impression were also identified.